Automatic motorbike accident detection and notification system - Siam, S.M. Kayser Mehbub; Sumaiya, Khadiza Islam; Amin, Md. Rakib Al; Turjo, Tamim Hasan (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.